PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT ALUPRIMA PACIFIC INDUSTRIES JAKARTA BARAT - Winda Yermin Wati Waruwu; Endah Asmarawati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the effect of work discipline and work motivation on employee performance at PT Aluprima Pacific Industries, West Jakarta. This research employs a quantitative research method with an associative approach. The population of this study consists of all employees of PT Aluprima Pacific Industries, West Jakarta, with a total sample of 40 employees, using a saturated sampling technique. The data collection method used was a questionnaire. The results of the analysis indicate that work discipline has a positive and significant effect on employee performance, with a simple linear regression equation of Y = 4.461 + 1.164X₁, a correlation coefficient of 0.865, which indicates a very strong relationship, and a coefficient of determination of 74.8%. This is proven by the t-test results where tₕᵢₜᵤₙg > tₜₐbₑₗ (13.895 > 1.669) and a significance value of 0.000 < 0.05. Work motivation also has a positive and significant effect on employee performance, as shown by the simple linear regression equation Y = 16.845 + 0.445X₂, a correlation coefficient of 0.695, indicating a strong relationship, and a coefficient of determination of 48.3%, which is supported by the t-test results (7.796 > 1.669) and a significance value of 0.000 < 0.05. Simultaneously, the results show that work discipline and work motivation have a positive and significant effect on employee performance, as indicated by the multiple linear regression equation Y = 3.275 + 0.951X₁ + 0.162X₂, a correlation coefficient of 0.877, which indicates a strong relationship, and a coefficient of determination of 78.7%. This is evidenced by the F-test results (118.198 > 3.140) and a significance value of 0.000 < 0.05, therefore Ho is rejected and Ha is accepted. Keywords: Work Discipline, Work Motivation, Employee Performance